The Effect of the Problem Based Learning (PBL) Model on Student Activities and Learning Outcomes on Excretory System Materials in Grade VIII of SMP Negeri 2 Percut Sei Tuan - Heni Nathali Rosa Sibarani; Marlinda Nilan Sari Rangkuti (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
This study aims to determine the effect of problem-based learning (PBL) model on students' activities and learning outcomes on human excretory system material in class VIII SMP Negeri 2 Percut Sei Tuan. This research uses quantitative methods with a pseudo-experimental approach. The research design used was non-equivalent control group. The study population included all VIII grade students of SMP Negeri 2 Percut Sei Tuan, consisting of 11 classes. The research sample was selected using purposive sampling technique, class VIII-6 as the experimental class and class VIII-7 as the control class. The average pre-test and post-test data of cognitive abilities in the experimental class were 33.6 and 83 and in the control class were 33.8 and 78.3. Based on hypothesis testing, for the experimental class and control class obtained tcount = 4.1308 and ttable = 2.0017, then tcount > ttable. The results of observations of student activity from meeting one to meeting three have increased, in the experimental class is 63.62% and in the control class is 58.73%, it is concluded that there is an effect of the problem-based learning (PBL) model on student activity and learning outcomes on the material of the human excretory system.